Kejadian Bendungan ASI pada Ibu Postnatal Care: Literature Review - Wijayanti, Ika (Journal of Midwifery Science: Basic and Applied Research, 2024)
Background: The postpartum period is a transition period from intranatal to postnatal, during this period the problems that often occur, one of which is breast milk dams caused by narrowing of the lacteferous ducts by glands that are not emptied completely so that venous and lymphatic flow is blocked, this causes The breasts are swollen and very painful, to overcome this you can do breast massage (breast massage). Objective: of this research is to determine the effect of lactation massage on breast milk retention in post partum mothers at RSIA Khadijah 1 Makassar. Method: This research is a type of quantitative research with a quasi-experimental design, with a pre-test and post-test with control group design approach. The population in this study was post partum mothers at RSIA Sitti Khadijah I Makassar in June 2018 using accidental sampling technique. The total sample was 16 post partum mothers who were given breast massage intervention for 3 days with a duration of 15 minutes. The data analysis used was bivariate analysis using the Paired Sample T test. Results: Based on the research results before breast massage was carried out, of 16 post partum mothers there were 81.3% or 13 post partum mothers who were categorized as having breast milk dams and after lactation massage there was a decrease in breast milk dams from 81.3% to 18.8% . Conclusions and Suggestions: There is an effect of Lactation Massage on breast milk dams with a ρ.Value of 0.007. It is hoped that you will continue to carry out breast massage both before and after giving birth to avoid breast milk dams and facilitate the release of breast milk as early as possible.